Family caregivers require mental health specialists for end‐of‐life psychosocial problems at home: a nationwide survey in Japan. Issue 6 (14th September 2015) - Kobayakawa, Makoto; Okamura, Hitoshi; Yamagishi, Akemi; Morita, Tatsuya; Kawagoe, Shohei; Shimizu, Megumi; Ozawa, Taketoshi; An, Emi; Tsuneto, Satoru; Shima, Yasuo; Miyashita, Mitsunori
Abstract: Background: Psychological distress is problematic for patients and their family caregivers in the oncological setting. The level of stress is influenced by the health status of the patient and their family members as well as the support system for home care. However, it remains unclear how best to support distressed caregivers providing end‐of‐life care at home. Methods: The present study was performed as part of the Japan Hospice and Palliative Care Evaluation study among caregivers whose family members are provided home palliative care. The caregivers were asked whether they wished to receive psychological support from mental health specialists, and factors associated with the need for psychological support were analyzed. Results: Of the 1052 caregivers, 628 completed the questionnaire. As a whole, 169 subjects [27%; 23–30% (95% confidence interval)] reported needing psychological support from a mental health specialist. According to a multiple regression analysis, factors associated with the need for psychological support included (1) emotional distress due to the need to adapt to rapid worsening of the patient's condition [adjusted odds ratio: 2.62 (95% CI 1.77–3.88), p  < 0.001], (2) the poor health conditions of the caregivers [2.93 (1.61–5.36), p  < 0.001], and (3) having someone else available to care for the patient in place of the caregiver [0.51 (0.34–0.78), p  = 0.002]. Conclusions: Psychological support is required for caregivers tending to patients at home. Further studies are needed to construct a system to provide continuous support to caregivers. Copyright © 2015 John Wiley & Sons, Ltd.